1998
DOI: 10.2307/3237115
|View full text |Cite
|
Sign up to set email alerts
|

Sampling strategies for the assessment of tree species diversity

Abstract: Abstract. This paper aims at proposing efficient vegetation sampling strategies. It describes how the estimation of species richness and diversity of moist evergreen forest is affected by (1) sampling design (simple random sampling, random cluster sampling, systematic cluster sampling, stratified cluster sampling); (2) choice of species richness estimators (number of observed species vs. non‐parametric estimators) and (3) choice of diversity index (Simpson vs. Shannon). Two sites are studied: a 28‐ha area sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 32 publications
0
75
0
3
Order By: Relevance
“…Magurran (1988) indicated that a Re´nyi series value with larger scale parameter value has reduced sensitivity to sample size. Gimaret-Carpentier et al (1998) observed that the Simpson index reached stable values at lower sample sizes compared to the Shannon index.…”
Section: Using Diversity and Evenness Profilesmentioning
confidence: 90%
“…Magurran (1988) indicated that a Re´nyi series value with larger scale parameter value has reduced sensitivity to sample size. Gimaret-Carpentier et al (1998) observed that the Simpson index reached stable values at lower sample sizes compared to the Shannon index.…”
Section: Using Diversity and Evenness Profilesmentioning
confidence: 90%
“…A análise faunística do atendimento de formicídeos e dos predadores foi realizada através dos índices de riqueza (Jacknnife) (giMaret-carPentier et al 1998), diversidade (H') (Shannon-Wiener), Simpson (D), equitabilidade J (e) (Brower et al 1997) …”
Section: Methodsunclassified
“…It is known that the number of observed forest tree species in regional or national forest monitoring programs typically underestimates the actual number of forest species present in the sampled forests (Cao, et al, 2004;Chiarucci, et al, 2003;Gimaret-Carpentier, et al, 1998;Hellmann & Fowler, 1999;Hwang & Shen, 2010;Lam & Kleinn, 2008;Magnussen & Boudewyn, 2008). The exceptions are in forests with few relatively rare species and in the absence of rare forest tree species.…”
Section: Journal Of Environment and Ecologymentioning
confidence: 99%
“…Estimating forest tree species richness from a forest inventory (monitoring) sample is a complex challenge with important issues related to temporal changes in the sample frame (Lister & Scott, 2009), sample size (Brose, Martinez, & Williams, 2003;Cao, et al, 2004;Hortal, Borges, & Gaspar, 2006), plot size (Brose, et al, 2003;Gimaret-Carpentier, Pelissier, Pascal, & Houllier, 1998;Shen & He, 2008), species identification (Archaux, 2009;Archaux et al, 2009), and choice of estimator (Mao & Lindsay, 2007;Walther & Morand, 1998). This study only deals with the last issue but fully recognizes that its importance depends critically on having satisfactory addressed all the other issues first.…”
Section: Introductionmentioning
confidence: 99%